STRUCTURE AND PHASE COMPOSITION OF THE SURFACES RECOVERED BY ELECTROSPARKING COATINGS. RESULTS OF MICROSTRUCTURAL AND X-RAY DIFFRACTION ANALYSIS - Tamargazin, А. А.; Brusilo, Y. V.; Puhachevska, Е. P. Puhachevska (Science-based technologies, 2016)
The investigation results of structure and phase composition of surfaces recovered by electrosparking spraying at transportation of spraying particles by air and combustion products of propane-air mixture have been discussed in the article. It was shown that the structure of coating at electrosparking spraying represents itself heterogeneous system consisting of two and more phases separating between each other by interface and differ by chemical compound and properties. This allows to obtain recovered surfaces with set complex of operating properties and to solve the problem of resource control of recovered details by controlling spraying of recovered coatings from iron-carbon alloys regulating its structure-phase changes. The process of electrosparking spraying at wire steels spraying by compressed air has more low temperature of melted particles and their big size resulted to bigger burning of alloying elements in it and oxidation of spraying layers in comparison with layers made by spraying of these wire materials by combustion products of propane-air mixture. нных между собой границей раздела и отличающихся между собой по химическому составу и свойствам. Это в свою очередь позволяет получать восстанавливаемые поверхности с требуемым комплексом эксплуатационных свойств и тем самым решить проблему управления ресурсом восстановленных деталей покрытиями из железо-углеродистых сплавов, посредством управление структурно-фазовыми превращениями в этих покрытиях в процессе их нанесении на восстанавливаемую деталь. При распылении проволочных сталей сжатым воздухом процессу электродугового напыления присущи относительно более низкая температура расплавленных частиц и их больший размер, что приводит к большему выгоранию в них легирующих элементов и окислению напыляемых слоев по сравнению со слоями, полученными при распылении этих проволочных материалов продуктами сгорания пропано-воздушной смеси.